2017
DOI: 10.3390/f8030091
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Plasticity Explains Response Patterns of European Beech (Fagus sylvatica L.) Saplings to Nitrogen Fertilization and Drought Events

Abstract: Climate and atmospheric changes affect forest ecosystems worldwide, but little is known about the interactive effects of global change drivers on tree growth. In the present study, we analyzed single and combined effects of nitrogen (N) fertilization and drought events (D) on the growth of European beech (Fagus sylvatica L.) saplings in a greenhouse experiment. We quantified morphological and physiological responses to treatments for one-and two-year-old plants. N fertilization increased the saplings' abovegro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…The mechanisms by which excess N supply can cause a net decrease in tree vitality can be complex, interlinked and only episodically apparent, including increased susceptibility to insect attacks, pathogens, frost and storm damages (Bobbink and Hettelingh, 2011), changes in mycorrhiza (Arnolds, 1991;Braun et al, 2010;De Witte et al, 2017;Duquesnay et al, 2000;Jaenike, 1991;van der Linde et al, 2018), changes in the rooting system and aluminum toxicity to roots (Dziedek et al, 2017;Godbold and Kettner, 1991;Haynes, 1982;Jonard et al, 2012;Ostonen et al, 2007), depletion of base cations due to NO3leaching (Jonard et al, 2012;Prietzel et al, 1997) or problematic P supply (Jonard et al, 2015;Mellert and Ewald, 2014;Neirynck et al, 1998;Ochoa-Hueso et al, 2013;Peñuelas et al, 2013;Sardans et al, 2015;Sardans and Peñuelas, 2012;Thelin et al, 1998). Tree species, stand age, soil, and meteorological conditions as well as other local factors co-determine these symptoms.…”
Section: Mechanisms Of N-induced Effects On Vitalitymentioning
confidence: 99%
“…The mechanisms by which excess N supply can cause a net decrease in tree vitality can be complex, interlinked and only episodically apparent, including increased susceptibility to insect attacks, pathogens, frost and storm damages (Bobbink and Hettelingh, 2011), changes in mycorrhiza (Arnolds, 1991;Braun et al, 2010;De Witte et al, 2017;Duquesnay et al, 2000;Jaenike, 1991;van der Linde et al, 2018), changes in the rooting system and aluminum toxicity to roots (Dziedek et al, 2017;Godbold and Kettner, 1991;Haynes, 1982;Jonard et al, 2012;Ostonen et al, 2007), depletion of base cations due to NO3leaching (Jonard et al, 2012;Prietzel et al, 1997) or problematic P supply (Jonard et al, 2015;Mellert and Ewald, 2014;Neirynck et al, 1998;Ochoa-Hueso et al, 2013;Peñuelas et al, 2013;Sardans et al, 2015;Sardans and Peñuelas, 2012;Thelin et al, 1998). Tree species, stand age, soil, and meteorological conditions as well as other local factors co-determine these symptoms.…”
Section: Mechanisms Of N-induced Effects On Vitalitymentioning
confidence: 99%
“…Further study is needed to explore the impact of precipitation changes on the productivity of grassland ecosystems. In addition, human industrial and agricultural activities led to a sharp increase in atmospheric nitrogen (N) deposition (Fowler et al 2013;Galloway et al 2008), resulting in the accumulation of available nitrogen, which is gradually improving productivity (Dziedek et al 2017;Epstein et al 2002). The restriction of other elements caused by nitrogen enrichment further counteracts the positive effect of nitrogen increase on plant growth (Wang et al 2018;Zhan et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Meta‐analysis of 164 studies suggested that sensitivity of within‐plant organ allometry is common: drought experiments altered plant biomass partitioning ratios, favouring root over shoot biomass and altering ratios of reproductive to vegetative biomass (Eziz et al, ). Similarly, treatments such as competition (Yu & Gao, ) or nitrogen addition (Dziedek et al, ) can alter patterns of biomass partitioning (but see Bernacchi, Coleman, Bazzaz, & McConnaughay, ; Peng & Yang, ). While experimental approaches are useful for detecting whether or not allometry is invariant, they do not capture the continuous variation in allometry that characterizes natural systems under variable climate regimes.…”
Section: Introductionmentioning
confidence: 99%